Enhancing the Electrochemical Doping Efficiency in Diketopyrrolopyrrole‐Based Polymer for Organic Electrochemical Transistors. (9th November 2020) - Wu, Xihu; Liu, Qian; Surendran, Abhijith; Bottle, Steven E.; Sonar, Prashant; Leong, Wei Lin
Abstract: The increasing interest in organic electrochemical transistors (OECTs) for next‐generation bioelectronic applications motivates the design of novel conjugated polymers with good electronic and ionic transport. Many conjugated polymers developed for organic field‐effect transistors (OFETs) exhibit high charge carrier mobilities but they are not suitable for OECTs due to poor ion‐uptake arising from the non polar alkyl chain substituted on the conjugated backbone. They are also sensitive to moisture, resulting in poor performance in aqueous electrolytes. Herein, the widely used conjugated building block diketopyrrolopyrrole (DPP) is used and functionalized it with polar triethylene glycol side chains (PTDPP‐DT) to promote ion penetration. The electrical performance of PTDPP‐DT based OECT in two types of aqueous electrolytes is studied and the electrochemical doping response is investivated. It is found that the tetrafluoroborate (BF4 − ) anion with large crystallographic radius allows high‐efficiency electrochemical doping of the PTDPP‐DT polymer, and thus gives rise to the high transconductance of 21.4 ± 4.8 mS with good device stability, where it maintained over 91 % of its doped‐state drain current after over 500 cycles of pulse measurement. Abstract : A new diketopyrrolopyrrole (DPP)‐based copolymer bearing polar triethylene glycol side chains (PTDPP–DT) for organic electrochemical transistors (OECTs) is presented. The electrical performance of PTDPP–DT‐based OECT in two types of aqueous electrolytes (BF4 − and Cl − as anions) is studied and the electrochemical doping response is investigated.